Confirmation of OH as good thermometric species for gas temperature determination in an atmospheric pressure argon plasma jet. (12th June 2017) - Bazavan, M; Teodorescu, M; Dinescu, G
Abstract: We have proved that the temperatures determined from OH rotational spectra accurately describe the actual gas temperatures in an atmospheric pressure argon plasma jet, expanding in a hot ambient atmosphere. For this, we have operated the radiofrequency jet discharge inside a heated oven at various decreasing forwarded powers and increasing gas flow rates. We compared the rotational temperature values with the temperature of the oven. When extrapolated to zero power or infinite gas flow, the data describing the dependence of the rotational temperatures upon power and mass flow rate indicate the correct oven temperature. We demonstrate that the population of the rotational levels of the OH molecule is in equilibrium with the translational motion of the argon atoms in the plasma jet, from room temperature (RT) to 500 °C.